O YouTube e o Cyberbullying de alunos contra professores around the world (YouTube and Cyberbullying of students against teachers around the world) - Zuin, Antonio Alvaro Soares (Revista Eletrônica de Educação, 2017)
The teacher, in one way or another, has always been identified as a pedagogical authority. But if there were a society whose technological development determined radical transformations in the production and dissemination of knowledge, to the point of decisively changing the relations between teachers and students? Would the teacher continue to represent a model of identity for the student who could access information online in any time and space? In view of the context of the digital culture society, the objective of this article is to investigate how students practice cyberbullying in relation to their teachers through images recorded by mobile phones, which are posted on the site YouTube. It will be analyzed three videos posted by students from three different countries (Brazil, Portugal and England), whose images refer to situations experienced with their respective teachers. It is also intended to argue that such attitudes are signs of radical transformations that are occurring in relation to the way students identify the teacher as a pedagogical authority. Key-words: Digital culture, Cyberbullying, YouTube, Cellphones. Resumo O professor, de uma forma ou de outra, sempre foi identificado como autoridade pedagógica. Mas, e se houvesse uma sociedade cujo desenvolvimento tecnológico determinasse transformações radicais na produção e disseminação do conhecimento, a ponto de se alterar, de forma decisiva, as relações entre professores e alunos? O professor continuaria a representar um modelo de identidade para o aluno que pudesse acessar informações de forma online em quaisquer tempos e espaços? Diante do contexto da sociedade da cultura digital, destaca-se o objetivo deste artigo: investigar o modo como alunos praticam cyberbullying em relação a seus professores por meio de imagens gravadas por telefones celulares, as quais são postadas no sítio de compartilhamentos de imagens e comentários chamado YouTube. Serão analisados três vídeos postados por alunos de três diferentes países (Brasil, Portugal e Inglaterra), cujas imagens se referem a situações vivenciadas com seus respectivos professores. Pretende-se, ainda, argumentar que tais atitudes são indícios de transformações radicais que estão ocorrendo em relação ao modo como os alunos identificam o professor como uma autoridade pedagógica. Palavras-chave: Cultura digital, Cyberbullying, YouTube, Celulares. References: HINDUJA, Sameer; PATCHIN, Justin. Bullying, cyberbullying, and suicide, Arquives of Suicide Research, 14, 206-221, 2010. KYRIACOU, Chris. Helping Troubled Pupils, Cheltenham: Nelson Thornes, 2003. KYRIACOU, Chris. Effective teaching in schools: theory and practice, Cheltenham: Stanley Thornes, 2009. KYRIACOU, Chris; ZUIN, Antônio. Cyberbullying of teachers by students on YouTube: Challenging the image of teacher authority in the digital age. Research Papers in Education, v.1, p.1-19, 2015. LIVINGSTONE, Sonia. Taking risky opportunities in youthful content creation: teenagers’ use of social networking sites for intimacy, privacy, and self-expression, New Media Society, 10, 393-411, 2009. O’HIGGINS, James Norman; CONNOLLY, John. Mimetic theory and scapegoating on the age of cyberbullying: the case of Phoebe Prince. Pastoral Care in Education, 29 (4), 287-300, 2011. TÜRCKE, Christoph. Sociedade excitada: filosofia da sensação. Campinas: Unicamp, 2010. TÜRCKE, Christoph. Vício e fundamentalismo. In: ZUIN, Antônio, LASTÒRIA, Luiz A.; GOMES, Luiz Roberto. Teoria crítica e formação cultural: aspectos filosóficos e sociopolíticos. Campinas: Autores Associados, 2012. WEI, Fang-Yi; WANG, Ken. Student’s silent messages: can teacher verbal and nonverbal immediacy moderate student use of text messaging in class?, Communication Education, 59 (4), 475-496, 2010. ZUIN, Antônio. Violência e tabu entre professores e alunos: a internet e a reconfiguração do elo pedagógico, São Paulo: Cortez, 2012.